85. EEG automated analysis compared to direct vision in ION setting: An overall impression. Issue 4 (April 2016) - Foresti, C.; Frigeni, B.; Furnari, A.; Salmaggi, A.; Stanzani, L.; Venturelli, E.; Rottoli, M.R.
Abstract : The automated analysis is an alternate representation of the raw EEG traces to deliver a more compacted form of information to clinicians, in order to quickly understand a large amount of data for the diagnostic purposes. Also ION instruments have the possibility to perform similar automatic analysis to provide visual or audible warning messages during surgical procedures. Anyway clinician's primary concern is whether false alarms or true positives might create a useful and reliable tool for detection and diagnosis. We compared automatic EEG analysis to expert physician visual direct examination in some different condition (carotid endo-arterectomy; MAV surgery; exclusion of intracranial aneurism; carotid-media artery by-pass). The automated analysis was performed through an algorithm based on Fourier spectral transform. Compared to early and accurate expert physician surveillance, this framework showed a good but delayed sensitivity in detecting significant neural activity modifications. Our overall impression is that direct visual EEG evaluation still represents the most consistent monitoring system. Although creating an algorithm that produces correct results in all instances is nearly impossible, the EEG automated analysis pitfall is yet a lack of a prompt processing of data trending, so as to fit the aim of ION procedure about timely warning messages.